Story of survival in anaplastic large cell lymphoma - sometimes more than the anaplastic lymphoma kinase status: An evaluation of pathologic prognostic factors in 102 cases - Komal Agrawal; Tanuja Shet; Epari Sridhar; Suhas Dhende; Manju Sengar; Brijesh Arora; Siddhartha Laskar; Sumeet Gujral; Hari Menon; Shripad Banavali (Wolters Kluwer Medknow Publications, 2017)
Introduction: Systemic anaplastic large cell lymphoma (ALCL) accounts for 5%-10% of adult non Hodgkin's lymphoma (NHL) and 10%-30% of childhood NHL. Owing to significant differences in survival and gene expression profile, current WHO classifies ALCL into two distinct entities as anaplastic lymphoma receptor tyrosine kinase (ALK) positive and ALK negative ALCL with ALK expression by tumour as a good prognostic indicator. However, in our institute which is a cancer referral institute, our preliminary experience was that even ALK positive tumours did not fare well as compared to ALK- negative ALCL. So, the current study aims at exploring more clinical and pathological factors impacting survival in ALCL patients. Objective: To study clinical and pathological prognostic factors in cases of ALCL. Methods: 102 cases of ALCL were retrieved from pathology database. Pathological features and clinical features of these cases were recorded and factors found to impact overall survival (OAS) and disease-free survival (DFS) curves were identified based on univariate and multivariate analysis. Results: ALK 1 expression was seen in 71/102 (69.6%) cases and was not found to impact OAS or DFS. The 2 year OAS rate for ALK positive patients was 63.5% and DFS rate was 54.4%, while for ALK negative patients, the OAS was 60.5% and DFS was 43.5%. The Ann Arbor stage, performance status, international prognostic index, histological subtype, and the degree of the background inflammatory infiltrate were found to impact the OAS significantly. Increased reactive inflammatory component also negatively impacted DFS. In the multivariate analysis, only the histologic type emerged as significant for OAS. Conclusion: Though ALK plays a role in prognostication of systemic ALCL, advanced stage disease and an inflammatory milieu may modulate the final outcome. We report a study of clinical and pathologic prognostic features in 102 cases of anaplastic large cell lymphoma (ALCL) from a cancer referral institute in India. Anaplastic lymphoma receptor tyrosine kinase (ALK-1) expression was seen in 71/102 (69.6%) cases and was not found to impact overall survival (OAS) or disease-free survival (DFS). The 2-year OAS rate for ALK-positive patients was 63.5% and DFS rate was 54.4%, while for ALK-negative patients, the OAS was 60.5% and DFS was 43.5%. The Ann Arbor stage, performance status, international prognostic index, histological subtype, and the degree of the background inflammatory infiltrate were found to impact the OAS significantly. Increased reactive inflammatory component also negatively impacted DFS. In the multivariate analysis, only the histologic type emerged as significant for OAS. Thus, though ALK plays a role in prognostication of systemic ALCL, advanced stage disease and an inflammatory milieu may modulate the final outcome.